2012
DOI: 10.1371/journal.pone.0039614
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Induced Increase in Methane Release from Peat Bogs: A Mesocosm Experiment

Abstract: Peat bogs are primarily situated at mid to high latitudes and future climatic change projections indicate that these areas may become increasingly wetter and warmer. Methane emissions from peat bogs are reduced by symbiotic methane oxidizing bacteria (methanotrophs). Higher temperatures and increasing water levels will enhance methane production, but also methane oxidation. To unravel the temperature effect on methane and carbon cycling, a set of mesocosm experiments were executed, where intact peat cores cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 15 publications
1
52
0
Order By: Relevance
“…) and previous work has shown that both warming (van Winden et al . ) and vegetation (Levy et al . ; Gray et al .…”
Section: Discussionmentioning
confidence: 99%
“…) and previous work has shown that both warming (van Winden et al . ) and vegetation (Levy et al . ; Gray et al .…”
Section: Discussionmentioning
confidence: 99%
“…Rising temperatures are likely to stimulate aerobic CH 4 oxidation (He et al, ; Kip et al, ; Knoblauch et al, ; Metje & Frenzel, ). However, mesocosm experiments indicate that temperature‐induced increases in CH 4 production cannot be fully compensated by methanotrophy, observing a drop of 98% to 50% oxidation efficiency from 5 to 25°C (van Winden et al, ), possibly due to lower CH 4 solubility at higher temperatures increasing the occurrence of ebullition over diffusion. The importance of anaerobic methanotrophs (see section 2.2) is not yet well explored at low temperatures, although this process could contribute to CH 4 consumption in permafrost soils (Kao‐Kniffin et al, ).…”
Section: Permafrostmentioning
confidence: 99%
“…A semi-arid study in Northern China by Hou et al, (2012) observed a linear correlation between temperature and the uptake of methane in the months of July and August with R 2 = 0.8357 and 0.6337 respectively. On the other hand, a UK experimental study in the Moor house Nature reserve (North Pennines) show that 98% of methane is retained at 5 0 C but as temperature increased to 25 0 C only 50% could be retained (Winden et al, 2012). An empirical study is fundamental to our understanding of how CH 4 might respond to temperature variability specifically in the tropics and this could be vital in determining the best possible geoengineering scheme to reduce temperature anomalies since it is impossible to control other parameters like precipitation, wind.…”
Section: Uncertainties and Errors In Estimated Methane Emissions Frommentioning
confidence: 99%